In search of ideal donor site wound dressings - Sharma, Dev Jyoti; Mishra, Bharat; Arora, Chetna (International Surgery Journal, 2020)
Background: Split skin grafting (SSG) is a commonly used reconstructive technique for wound cover. Donor site wounds (DSW) after split-skin graft harvesting are rather clean wounds. Depending on the thickness of the SSG, the DSW should re-epithelialize completely in 7 to 21 days. This study was initiated with a background to look for an ideal dressing for the management of DSW. Aim of the study was to compare efficacy of Cellulose acetate mesh, Collagen sheet, Hydrocolloid dressings and chlorhexidine tulle for donor site wound management after harvesting split thickness skin graft. Methods: 100 patients with 100 donor site wounds were included in the study. Patients were randomized into four different groups of 25 each, depending upon the type of dressings used to cover the wound. Data regarding time to complete wound healing and pain at the donor site were recorded on visual analogue scale (VAS). Requirement of pain killers during post-operative period were recorded. Complications like infection or hyper-granulation were also recorded. Results: The study included 72 males and 28 females. The primary objective was to observe the effectiveness of wound dressings in the treatment of DSWs and time to complete wound healing. In this context, collagen dressing was found to be the most effective in current study (p<0.07) and also the least pain was experienced by the patients where collagen dressings were used. Conclusions: The study concluded that collagen dressings was best amongst the various dressings studied with average healing time of 9 days with least pain score over DSW.